Plowshares : Protest, Performance, and Religious Identity in the Nuclear Age - Tobey, Kristen, 1978- (Book collections on Project MUSE., 2016)
"Explores the actions of the radical Roman Catholic antinuclear activist group Plowshares. Focuses on the closely interwoven religious and social significance of the group's actions and subsequent legal trials, which rely on performances of moral distinction to achieve the activists' aims"--Provided by publisher